THE ASSOCIATION BETWEEN AUDIT FEE AND AUDIT QUALITY: A META-ANALYSIS STUDY - Hartaty, Hartaty; Dianawati, Wiwiek (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2024)
Introduction: This study aims to reconcile conflicting empirical results from previous studies on the relationship between audit fees and audit quality. In addition, it investigated whether the contradictory findings were moderated by different types of audit fees and audit quality measures. The study also makes cross-country comparisons of empirical evidence to provide more insights. Methods: This study utilized meta-analysis to integrate the findings of previous studies on the relationship between audit fees and audit quality and further investigated moderators of the association. Results: The findings revealed that audit fees had a positive effect on audit quality. These results were observable for both developed and developing countries, indicating the beneficial consequences of audit fees on audit quality should not be overlooked. Furthermore, this study also found that the size of audit fees and quality moderated the positive influence of audit fees on the quality. Conclusion and suggestion: This study contributes to the stream of research investigating the relationship between audit fees and audit quality. To the best of our knowledge, this study represents one of the pioneering efforts to apply statistical meta-analysis to the issue addressed.